Interactions of Neanderthals and Modern Humans: What Can Be Inferred from Mitochondrial DNA? - Krzysztof A. Cyran; Marek Kimmel (Mathematical Biosciences and Engineering)
This paper reviews the state-of-the-art knowledge concerning the relationship between Neanderthals and Upper Paleolithic modern humans. The branching-process method is applied to infer the upper limit of hypothetical Neanderthal admixture, consistent with the evidence based on mitochondrial DNA sequences of contemporary modern humans, as well as Neanderthal and early modern European H. sapiens fossils. As a result, a maximum value of 15% admixture is obtained. This estimate is discussed in the context of its consequences for the two competing theories of modern human origin.